Ecological similarity explains species abundance distribution of small mammal communities - Hidasi-Neto, José; Bini, Luis Mauricio; Siqueira, Tadeu [UNESP]; Cianciaruso, Marcus Vinicius (Elsevier, 2020)
For several decades, ecologists have been trying to explain how species abundance distributions (SAD) emerge within communities. Niche models predict that species habitat requirements and life-history traits determine SADs. Here, based on predictions from a well-known niche-based SAD (Sugihara's model), we tested whether abundant species are ecologically less similar among each other than less abundant ones, and whether the strength of this relationship is reduced in high productivity areas. Using species abundance and trait data from 88 small mammal communities around the world we found that the most abundant species are similar to other abundant species, but less similar to rare species. However, this relationship is weakened in high-productivity areas, such as the tropics. These results suggest that niche differences moderate species abundances, and that low-productivity habitats have a reduced ecological space, especially for specialist species. A next step to uncover biological processes underlying the formation of SADs is to understand how they are influenced by the order of species arrivals during the assembly of communities.
Keywords: Functional traits; Niche space; SAD; Species abundance